Beneficial metabolic effects of recurrent periods of beta‐cell rest and stimulation using stable neuropeptide Y1 and glucagon‐like peptide‐1 receptor agonists. Issue 12 (11th August 2022) - Tanday, Neil; Lafferty, Ryan A.; Flatt, Peter R.; Irwin, Nigel
Abstract: Aim: To examine whether sequential administration of (d ‐Arg 35 )‐sea lamprey peptide tyrosine tyrosine (1–36) (SL‐PYY) and the glucagon‐like peptide‐1 (GLP‐1) mimetic, liraglutide, has beneficial effects in diabetes. Methods: SL‐PYY is an enzymatically stable neuropeptide Y1 receptor (NPY1R) agonist known to induce pancreatic beta‐cell rest and improve overall beta‐cell health. We employed SL‐PYY and liraglutide to induce appropriate recurrent periods of beta‐cell rest and stimulation, to assess therapeutic benefits in high fat fed (HFF) mice with streptozotocin (STZ)‐induced insulin deficiency, namely HFF‐STZ mice. Results: Previous studies confirm that, at a dose of 0.25 nmol/kg, liraglutide exerts bioactivity over an 8‐12 hour period in mice. Initial pharmacokinetic analysis revealed that 75 nmol/kg SL‐PYY yielded a similar plasma drug time profile. When SL‐PYY (75 nmol/kg) and liraglutide (0.25 nmol/kg) were administered sequentially at 08:00 AM and 08:00 PM, respectively, to HFF‐STZ mice for 28 days, reductions in energy intake, body weight, circulating glucose, insulin and glucagon were noted. Similarly positive, but slightly less striking, effects were also apparent with twice‐daily liraglutide‐only therapy. The sequential SL‐PYY and liraglutide treatment also improved insulin sensitivity and glucose‐induced insulin secretory responses, which was not apparent with liraglutide treatment, although benefits on glucose tolerance were mild. Interestingly, combined therapy also elevated pancreatic insulin, decreased pancreatic glucagon and enhanced the plasma insulin/glucagon ratio compared with liraglutide alone. This was not associated with an enhancement of beneficial changes in islet cell areas, proliferation or apoptosis compared with liraglutide alone, but the numbers of centrally stained glucagon‐positive islet cells were reduced by sequential combination therapy. Conclusion: These data show that NPY1R‐induced intervals of beta‐cell rest, combined with GLP‐1R–stimulated periods of beta‐cell stimulation, should be further evaluated as an effective treatment option for obesity‐driven forms of diabetes.